Critical care medicine in the French Territories in the Americas: Current situation and prospects - Hatem Kallel; Dabor Resiere; Stéphanie Houcke; Didier Hommel; Jean Marc Pujo; Frederic Martino; Michel Carles; Hossein Mehdaoui (Pan American Health Organization, 2021)
Hospitals in the French Territories in the Americas (FTA) work according to international and French standards. This paper aims to describe different aspects of critical care in the FTA. For this, we reviewed official information about population size and intensive care unit (ICU) bed capacity in the FTA and literature on FTA ICU specificities. Persons living in or visiting the FTA are exposed to specific risks, mainly severe road traffic injuries, envenoming, stab or ballistic wounds, and emergent tropical infectious diseases. These diseases may require specific knowledge and critical care management. However, there are not enough ICU beds in the FTA. Indeed, there are 7.2 ICU beds/100 000 population in Guadeloupe, 7.2 in Martinique, and 4.5 in French Guiana. In addition, seriously ill patients in remote areas regularly have to be transferred, most often by helicopter, resulting in a delay in admission to intensive care. The COVID-19 crisis has shown that the health care system in the FTA is unready to face such an epidemic and that intensive care bed capacity must be increased. In conclusion, the critical care sector in the FTA requires upgrading of infrastructure, human resources, and equipment as well as enhancement of multidisciplinary care. Also needed are promotion of training, research, and regional and international medical and scientific cooperation.